mdbk : nullsechs nullsieben - Museum der bildenden Künste, Leipzig (Leipzig : Museum der bildenden Künste Leipzig, 2008)
(e.) Twin Gabriel ; Angelmaier, Claudia ; Baumgartner, Christiane ; Beckmann, Max ; Behrendt, Falko ; Bernstein, Friedrich Otto ; Bisky, Norbert ; Christo & Jeanne-Claude ; Doig, Peter ; Ebersbach, Hartwig ; Ebner, Florian ; Ecker, Bogomir ; Gaul, August ; Geers, Kendell ; Gille, Sighard ; Grahnert, Henriette ; Hartung, Hans ; Janssen, Horst ; Kauka, Rolf ; Klafki, Anja ; Klinger, Max ; Kobe, Martin ; Krohg, Christian ; Leger, Fernand ; Lewandowsky, Via ; Martinez Celaya, Enrique ; Mattheuer, Wolfgang ; Michailov, Boris ; Milev, Yana ; Muggenthaler, Johannes ; Nicolai, Carsten ; Penck, A.R. ; Polster, Ulrich ; Rauch, Neo ; Rautert, Timm ; Reinartz, Manuel ; Richter, Evelyn ; Rinke, Klaus ; Ruscha, Ed ; Schelde, Morten ; Schlingensief, Christoph ; Schmidt, Julia ; Schnell, David ; Schröter, Erasmus ; Schulz, Tilo ; Thiele, Günter ; Triegel, Michael ; Tübke, Werner
Duits
boek